PENGARUH CURRENT RATIO DAN DEBT TO TOTAL ASSET RATIO TERHADAP NET PROFIT MARGIN PADA PT. UNILEVER INDONESIA TBK - Rani, safrani (Universitas Muhammadiyah Palembang, 2021)
ABSTRACTThe purpose of this study is to determine the influence of Current Ratio (CR) and Debt To Total Asset Ratio (DAR) on Net Profit Margin (NPM) at PT Unilever indonesia Tbk. The research conducted in this study is associative. Purpose – The sample technique in this study is purposive sampling with consideration of the use of complete data updated / latest, namely from 2008 to 2019 as much as 12 years, in the form of current assets, current debt, total debt, total assets, profit after tax, net sales. The instruments in this study in the form of a table consisting of current assets, current liabilities, equities, assets and profit after tax, net sales related to the variables of this study data accessed through the website www.unilever.co.id listing in IDX.Design/methodology –The methods used for data analysis in this study are classic assumption test, multiple linear regression analysis, multiple correlation test, determination cofesien, and hypothesis test (f test and t test).Findings - The results and conclusions in this study current ratio is insignificant and has no effect on Net Profit Margin at Pt. Unilever indonesia Tbk. Debt To Asset Ratio is insignificant and has no effect on Net Profit Margin at Pt. Unilever indonesia Tbk. Current Ratio and Debt To Asset Ratio is insignificant and has no effect on Net Profit Margin at Pt. Unilever Indonesia Tbk.